Berber und Ibāḍiten - Strothmann, Rudolph (Der Islam, 1928)
Contents: on the thesis of Berber inclination towards Khārijism (258-262). The Ibāḍī realm in North Africa (263-279): rulers (263-264), territory (264-265), tribes (265-267), attitude to life (267), ideals (267-269), Ibāḍī Berber women (269-272), the state (272-273), the danger of state crisis (273-274), the importance of dogmatics and jurisprudence (274-277), the national language and religious language (277-278), interaction between Ibāḍism and Berberism (278-279). Strothmann quotes mainly from: Masqueray 1878a; Basset 1899; Gautier: L’islamisation de l’Afrique du Nord. Les siècles obscures du Maghreb, Paris: Payot, 1927, which follows Ibn Khaldūn: al-Duwal al-Islāmiyya fī ‘l-Maghrib (ed. de Slane); Shammākhī: Siyar; and sometimes from: Barrādī: Jawāhir; Warjlānī: K. al-Dalīl wa’l-Burhān.
Keywords: Ibadisme -- Afrique du Nord

Theologie und Gesellschaft im 2. und 3. Jahrhundert Hidschra: eine Geschichte des religiösen Denkens im frühen Islam - Ess, Josef van (De Gruyter, 1997)
pp. 171-177 (Ibāḍī theologians); pp. 259-271 (the Maghrib); p. 1056 (index: Khārijīs); p. 1060 (index: Ibāḍiyya)
Keywords: Ibadisme -- Afrique du Nord

Die Anfänge der Ibaditen in Nordafrika: der Beitrag einer islamischen Minderheit zur Ausbreitung des Islams - Schwartz, Werner (Studien zum Minderheitenproblem im Islam, 1983)
Keywords: Ibadisme -- Afrique du Nord

الاباضية في المغرب العربي - حسين, أحمد إلياس (مكتبة الضامري, 1992)
Keywords: Ibadisme -- Afrique du Nord

Les Ibadites en Afrique - Solal, Elsa (Université Lille 3, 1968)
Keywords: Ibadisme -- Afrique du Nord